Comparing the Quality of Cardiopulmonary Resuscitation Performed at the Over-the-Head Position and Lateral Position of Neonatal Manikin - Cheung, Po-Yin; Huang, Hongmei; Xu, Chenguang; Liu, Jiang-Qin; Ting, Joseph Y.; Wong, Rosanna; Lee, Winnie; Xue, Yin; Yi, Yanzhi (Frontiers in Pediatrics, 2020)
Background: Recent neonatal resuscitation guidelines suggest to perform chest compression (CC) at over-the-head (OTH) position instead of lateral position when further interventions including umbilical venous access are needed. Little information is available regarding the quality of cardiopulmonary resuscitation at different positions. Our study compared the quality of CC and ventilation at OTH position vs. lateral position in simulated neonatal resuscitation. Methods: Thirty-nine neonatal practitioners who attended the NRP®-based Provider renewal course workshop participated this study. Laerdal QCPR infant model were used to collect the data (2-miutes continuous recording) on quality of CC and ventilation of all participants at OTH position and lateral position in randomized order, both coordinated with mask ventilation or endotracheal ventilation through a Neopuff© T-piece system. The quality of CC and ventilation were compared. Participants also reported their demographics and opinions in anonymous questionnaires after the session. Results: The quality of CC and ventilation was not different when CPR was performed at OTH position and lateral position, in both mask and endotracheal ventilation. When CPR was performed with endotracheal ventilation, there were small faster frequencies of CC and ventilation at OTH position, compared with those at lateral position (p=0.004). Most participants (87%) liked the CC performed at OTH position and had no adverse feedback. Conclusions: Performing CC at OTH position was generally well received in simulated resuscitation; the quality of CC and ventilation at OTH position was not significantly different from that at lateral position, irrespective of mask or endotracheal ventilation.